Untangling the inefficiency of hotel industry: The Portuguese Teixeira Duarte hotel chain analysis - Ferreira, N. B. (2022)
In this study the technical efficiency was analyzed for four hotels of the Teixeira Duarte Group - a renowned Portuguese hotel chain. An efficiency ranking was established for these four Portuguese hotels units using Stochastic Frontier Analysis. This methodology allowed discriminating between measurement error and systematic inefficiencies, enabling the identification of the main inefficiency causes. The results showed that distance to the airport and higher price of accommodations promote efficiency. Additionally, hotels with many standard rooms and sea views are likely to achieve higher levels of efficiency. These results should be carefully considered when aiming at improving hotel's efficiency, especially in Portuguese units with similar typology and location of the ones considered in this analysis.